Exhaled Breath Condensate in Childhood Asthma: A Review and Current Perspective - Bannier, Michiel A. G. E.; Rosias, Philippe P. R.; Jöbsis, Quirijn; Dompeling, Edward (Frontiers in Pediatrics, 2019)
Exhaled breath condensate (EBC) was introduced more than two decades ago as a novel, non-invasive tool to assess airway inflammation. This review summarizes the latest literature on the various markers in EBC to predict asthma in children. Despite many recommendations and two comprehensive Task Force reports, there is still large heterogeneity in published data. The biggest issue remains a lack of standardization regarding EBC collection, preservation, processing, and analysis. As a result, published studies show mixed or conflicting results, questioning the reproducibility of findings. Unless a joint, multicenter research study is initiated to address the necessary methodological standardization, another BRE(ATH)XIT may be imminent.